Investigation on solution properties of surfactants in mixed solvent media: Landmark towards Surface Chemistry in Eastern Nepal - Bhattarai, Ajaya (BIBECHANA, 2014)
Surfactants are amphiphilic molecules having a hydrophilic or water soluble moiety (head group) and a hydrophobic, or water insoluble moiety (tail group). Surfactants are not only related to soaps and detergents, they are also in heavy demand for industrial processes requiring colloid stability, metal treatments, mineral flotation, pesticides, oil production, pharmaceutical formulation, emulsion polymerization, particle growth and many more. That is why surfactants have been and continue to be a very active area of scientific research and commercial growth for several decades. One interesting property of surfactants is that at low concentrations, they exist solely as monomers. The formation of micelles, begins at a specific surfactant concentration termed the critical micelle concentration (cmc), where the physical properties of the solution, such as interfacial tension, electrical conductivity, and light scattering behaviour, often changes abruptly due to the existence of micelles. The formation of micelles will be able to calculate various thermodynamic parameters. These parameters make surfactants not only an interesting and rich area for the exploration of novel phenomena but also an area of research which can lead to new applications in a variety of fields. However, most of the previous studies on surfactants are limited to aqueous media only. Studies in mixed solvent media are very natural one as one can modulate the conformations of surfactants and their interactions easily by simply varying the composition of the media. With this concept, the research team of Eastern Nepal has started to work the solution properties of surfactants in different mixed solvent media in presence and absence of salts and has also investigated cationic and anionic surfactant interaction in mixed solvent media. DOI: http://dx.doi.org/10.3126/bibechana.v11i0.10400 BIBECHANA 11(1) (2014) 175-180